Substrate Integrated Waveguide Fed Cavity Backed Slot Antenna for Circularly Polarized Application - Xiao Hong Zhang; Guo Qing Luo; Lin Xi Dong (International Journal of Antennas and Propagation)
A novel planar low-profile cavity-backed slot antenna for circularly polarized applications is presented in this paper. The low-profile substrate integrated waveguide (SIW) cavity is constructed on a single PCB substrate with two metal layers on the top and the bottom surfaces and metallized via array through the substrate. The SIW cavity is fed by a SIW transmission line. The two orthogonal degenerate cavities resonance TM110 mode are successfully stimulated and separated. The circularly polarized radiation has been generated from the crossed-slot structure whose two arms’ lengths have slight difference Its gain is higher than 5.4 dBi, the peak cross-polarization level is lower than −22 dB, and the maximum axial ratio (AR) is about −1.5 dB. Compared with the previous presented low-profile cavity-backed slot antenna work, the spurious radiation from the proposed antenna’s feeding element is very low and it has less interference on the following circuits.